Kuatnya Jejak Ke-Austronesia-an pada Bahasa Bali Dialek Bali Aga - Dhanawaty, Ni Made (Jurnal Kajian Bali (Journal of Bali Studies); Vol 11 No 1 (2021): Volume 11 No. 1. April 2021DO - 10.24843/JKB.2021.v11.i01.p05, 2021)
The Balinese language is spatially divided into the Balinese dialect of Bali Aga (DBA) and the dialect of Bali Dataran (DBD). As a sub-family of Austronesian languages, the Balinese language has many features of being Austronesian. This study at analyzes the trace of the Bali Aga dialect, through four linguistic variables: the realization of the phoneme /a/, the distribution of phonemes /h/, bimonosilabel words, and personal pronouns. Data sources of this research are Balinese in the DBA area, general Balinese language, and Balinese inscriptions and dictionaries which were collected using the scrutinize and interview methods and analyzed by using comparative and distributional approaches. The results showed that the Austronesian traces in the Bali Aga dialect are still strong, indicated by (1) the persistence of [a] as a realization of the phoneme /a/ in the ultima position; (2) the persistence of /h/ in the initial and medial positions; (3) the persistence of penultima syllable coda on bimonosilabis words; (4) the persistence of Proto Austronesian pronouns. These indicate that the archaic data are very important in tracking language change.